Individual and psychological characteristics of law enforcement officers as a basis for effective psychological selection of personnel for modern police organizations - Okhrimenko, I.; Ostapovich, V.; Barko, V. V.; Barko, V. I.; Smirnova, O.; Hruzynska, I.; Marchenko, O.; ORCID: http://orcid.org/0000-0003-1007-9560 (BRAIN. Broad Research in Artificial Intelligence and Neuroscience. – 2022. – Vol. 13, Issue 4. – P. 141-162, 2022)
Метою дослідження є проведення порівняльного аналізу індивідуально-психологічних особливостей працівників правоохоронних органів, які здійснюють різні види правоохоронної діяльності.

The distinguishing features of a specific type of modern law enforcement activities (criminal police, patrol police, security police, pre-trial investigation bodies, district police officers) require a law enforcement officer to have certain individual and psychological characteristics, the absence of which make it impossible to successful perform their service tasks. Individual and psychological characteristics must be taken into account during the psychological selection of personnel for law enforcement agencies. The aim of the research is to undertake the comparative analysis of the individual and psychological characteristics of law enforcement officers who carry out various types of law enforcement activities. 986 law enforcement officers engaged in various types of law enforcement activities took part in the research. The research was carried out on the basis of a systematic approach using an optimal set of psychodiagnostic techniques. Professionally significant individual and psychological characteristics of law enforcement officers who undertake various types of service activities were singled out. It was found that the representatives of the criminal police and security police units are emotionally more stable compared to other categories of police officers. On the other hand, high levels of confidence, independence and leadership are expressed among patrol officers and investigators. Police officers in all types of law enforcement activities are particularly characterized by high self-control, responsibility, conscientiousness, thoroughness, and discipline. The obtained data will contribute to the improvement of the mechanism of psychological selection of personnel for modern police organizations.

Цель исследования - провести сравнительный анализ индивидуально-психологических особенностей сотрудников правоохранительных органов, осуществляющих различные виды правоохранительной деятельности.
Individual and psychological characteristics of law enforcement officers as a basis for effective psychological selection of personnel for modern police organizations / I. Okhrimenko, V. Ostapovich, V. V. Barko, V. I. Barko, O. Smirnova, I. Hruzynska, O. Marchenko // BRAIN. Broad Research in Artificial Intelligence and Neuroscience. – 2022. – Vol. 13, Issue 4. – P. 141-162. – DOI: https://doi.org/10.18662/brain/13.4/380.
Okhrimenko, I., Ostapovich, V., V. Barko, V., I. Barko, V., Smirnova, O., Hruzynska, I., & Marchenko, O. (2022). Individual and Psychological Characteristics of Law Enforcement Officers as a Basis for Effective Psychological Selection of Personnel for Modern Police Organizations. BRAIN. Broad Research in Artificial Intelligence and Neuroscience, 13(4), 141-162. https://doi.org/10.18662/brain/13.4/380.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; publikatsii u WoS; law enforcement activities; individual and psychological characteristics; police officers; psychological selection; правоохоронна діяльність; індивідуально-психологічні особливості; офіцер поліції; психологічний відбір; правоохранительная деятельность; индивидуально-психологические особенности; полицейский; психологический отбор